A case report on unusual cause of childhood obesity and visual disturbances-Bardet-Biedl syndrome - Panuganti, Suresh Kumar; Modi, Sujeeth Kumar; Patel, Pooja Nilesh; Boda, Sudha (International Journal of Research in Medical Sciences, 2024)
Bardet-Biedl syndrome (BBS) represents a rare genetic condition distinguished by a multifaceted set of clinical features, including obesity, retinal dystrophy, polydactyly, renal dysfunctions, and cognitive dysfunction. BBS mostly affects children of consanguineous marriages. It is frequently overlooked during initial pediatric examinations. The lack of syndromic diagnostic strategy for identifying genetic disorders by healthcare professionals is being acknowledged as a significant concern. Here, we reported a patient (9 year 4 months old male) born to second degree consanguineous parents, who presented with major features of Bardet-Biedl Syndrome (BBS). The patient came to us with the symptoms including increasing weight gain and visual disturbances. In our case, the diagnosis was made after a comprehensive clinical assessment and genetic testing. Genetic testing showed that the patient had a heterozygous missense variant of the BBS10 gene (chr12: g.76347012 C>A; Depth: 117x). This result confirmed the diagnosis of Bardet-Biedl-Syndrome. This case report highlights a patient diagnosed with BBS, focusing on the clinical manifestations, genetic characteristics and potential avenues for future research.